Usability evaluation of academic learning management system (ALMS): a pilot study - Abubakar, Mukhtar; Haizan Nor, Rozi Nor; Jaafar, Azmi (Science and Engineering Research Support Society, 2019)
Currently researchers concentrate on adaptive systems that have long been driven by pre-defined characteristics that represent individuals’ mental model for undertaking certain learning activities. However, different students are in possession of different state of cognition and emotion that have been extensively utilized as the way in the design of current Learning Management systems for academic purposes. The main goal of this study is to present a comprehensive preliminary study on adaptability/usability of an academic learning management system of UPM Learning Management System, based on usability factors of WAMMI and Nielsen.